Horse-riding simulator using a pneumatic actuation system for realistic motion replication and training applications - Ismail, Muainah; Abu Bakar, Mohd Khairul Fadzly (2025)
This project focuses on the design and development of a horse-riding simulator that uses compressed air pneumatic actuation to replicate the actual motions of horseback riding. The simulator aims to provide a realistic training experience for beginner and professional riders, enabling them to practice posture, balance, and coordination in a controlled environment. The use of a pneumatic system ensures smooth, adjustable, and repeatable motion profiles. The project includes mechanical design and pneumatic system integration with electrical technology. Traditional mechanical simulators often lack realism in motion replication, leading to the exploration of pneumatic actuation systems for smoother and more dynamic movements. Research and development of this project was conducted at Sekolah Kebangsaan Kampong Salang in collaboration with the Faculty of Mechanical Engineering and Technology, Universiti Malaysia Perlis.